The Analysis of Katajaga (Village of Qualified Family Latrine) Program Effect to The Contamination of Fecal Coliform , Diarrhea and Typhoid Occurrence in Semarang - Harahap, Maimunah; Laksono, Budi; Rustiana, Eunike Raffy (Universitas Negeri Semarang, 2018)
The most common contagious diseases in developing countries are diseases of the respiratory and digestive tract. Gastrointestinal tract infection disease can be caused by virus, bacteria and protozoa. Diseases that can occur include diarrhea and typhoid. Factors that may increase the risk of diarrhea and typhoid include fecal contaminated water and improper defecating. The lack of owning healthy latrines causes most of people defecate in any places which induce environmental pollution so that sanitation is needed to break the germ link from the infectious source. The purpose of this study is to analyze the effect of Katajaga program (Village Of Qualified Family Latrine) against contamination of fecal coliform, the occurrence of diarrhea and typhoid.This research is a type of quantitative research with cased control study approach. The population in this study was 30 people who were given Katajaga Program in Gunungpati Sub-district and 30 people who were not given Katajaga Program in Mijen Sub-district. Sampling was done by simple random sampling technique.The results showed that there was a significant difference of fecal coliform contamination rate between case and control group with p value 0.047 (p <0.05), there was a significant difference of diarrhea occurrence rate betweenÃ‚Â case and control group with p value 0.034 (p <0.05) and there was significant difference of typhoid occurrence rate between case and control group with p value 0.009 (p <0.05). The conclusion is giving the Katajaga program effects on the contamination of fecal coliform, the occurrence of diarrhea and typhoid. This research is useful to encourage people to improve sanitation development and prevent disease transmission caused by poor sanitary conditions.